Risk Factors for Dental and Oral Disease Abnormalities in Productive Age in Indonesia - I Gusti Ayu Ratih Pramesti; Anton Rahardjo; Iwany Amalliah Badruddin (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Oral diseases are among the most common diseases globally and have a serious health and economic burden, greatly reducing the quality of life for those affected. The most common oral diseases and considered a global public health priority are dental caries (tooth decay), periodontal disease, tooth loss, lip and oral cancer. Review: The method used in writing this article is Literature review, which is a literature search both internationally and nationally conducted using the Pubmed, Science Direct, and Proquest databases. In the initial stage, the search for journal articles was obtained from January 2013 to November 2023. The method used in writing this article is Literature review, which is a search for both international and national literature conducted using the Pubmed, Science Direct, and Proquest databases. In the initial stage of the search, journal articles were obtained from January 2013 to November 2023. A total of 1806 studies were potentially eligible and identified, finally, 10 studies were included for quality assessment 5-10 PRISMA flow chart of the literature selection process. After duplicates were removed and relevant studies were selected based on title and abstract, 43 full-text articles were retrieved and evaluated for eligibility. Of these, 24 articles were excluded based on the exclusion criteria, the remaining 10 studies investigated the relationship between dental health status and risk factors. The country of this study was Indonesia. The study subjects varied, with the age of the sample ranging from 10 years to 65 years. Conclusion: Most oral health conditions are largely preventable and treatable at an early stage. Oral diseases are caused by various modifiable risk factors common to many non-communicable diseases (NCDs). It is important to understand the etiological factors and pathogenesis of each dental health status to recognize and understand the associated risk factors. Periodontal disease, dental caries, dental erosion, fluorosis and oral cancer have multifactorial risk factors, effective disease management requires a clear understanding of all associated risk factors, almost all risk factors are significant to dental health status.